Political Marketing of the Gerakan Indonesia Raya (Gerindra) Towards 2024 Election - Happy Hervina; Asep Nurjaman (Budapest International Research and Critics University, 2022)
In a general election, political marketing as a strategy for political parties plays a very important role because it is part of the strategy of persuasion activities in the political marketing approach. This paper aims to explain the political marketing strategy of the Gerindra Party in facing the upcoming 2024 legislative election. In order to approach this problem, Adman Nursal's political marketing theory reference is used. The method used in this research is qualitative research with a qualitative descriptive approach. The data were collected through field studies and literature studies. Field studies to obtain primary data by conducting interviews. While library research to obtain secondary data based on books or other readings related to the research and then analyzed qualitatively. The results of this study indicate that the Gerindra Party of Jombang Regency has prepared a strategy in dealing with the 2024 General Election by conducting political research before carrying out the campaign, and the party machine through the structures in the Gerindra Party Branch Executive Board in Jombang Regency.